Analisis Keuntungan Relatif Dan Titik Impas Usahatani Kacang Hijau Di Kawasan Transmigrasi Desa Weoe Kecamatan Wewiku Kabupaten Malaka - Usman, Yusuf; Nurwiana, Ida; Bureni, Eman Nevianus (Buletin Ilmiah Impas, 2024)
Mung bean farming activities are often faced with low production by farmers. Farmers face a variety of problems, including annual increases in the price of labour, seeds, fertilisers, pesticides and output prices. Thus, improvements at the farm level and price stability are required. This helps to ensure increased income and profits for farmers, and will also encourage farmers to be more intensive in managing their farms. This study aims to: 1). Identify farmers' income from mung bean farming, 2). Knowing the relative profit of farmers from mung bean farming and 3). Knowing the break-even point obtained by farmers from mung bean farming in the Weoe Village Transmigration Area, Wewiku District, Malacca Regency. This research uses a survey method, the data used are primary data and secondary data. The research location in the Weoe Village Transmigration Area, Wewiku Sub-district, Malacca Regency was determined purposively, based on the potential for production development and the area of mung bean land. Samples were taken by simple random sampling of 60 respondents. The analysis method used income analysis, R/C ratio and Break Even Point. The results showed that, 1) the income obtained from mung bean farming was Rp 134,486,076 or Rp 5,655,428, -per hectare. 2) the relative profit obtained is 3.07, which means that the farm is economically profitable so it is feasible to develop, 3) the break-even point of production is 73.77 kg, meaning that when the production amount is 73.77 kg the mung bean farm is at the break-even point or the amount of production returns capital so that production of 875 kg/ha has exceeded the break-even point by 11 times in other words, it is profitable. While the price break-even point is Rp. 3,124/kg, meaning that when the selling price of peanuts is Rp. 3,124/kg, farmers have recovered their capital. With an average selling price of Rp. 14,683/kg, which exceeds the break-even point by more than 4 times, mung bean farming is in a profitable position.